Perancangan Data Warehouse Untuk Penerimaan Mahasiswa Baru - Munawar, Munawar (Lembaga Penerbitan Universitas Esa Unggul, 2013)
Data warehouse (DW) integrates information from numerous data sources not only for storage purposes but also for business analysis as well. As this information is to be used for business intelligent, it makes the design of DW difficult task. DW quality depends on the quality of all requirements, conceptual, logical and physical models used for DW design. Therefore, data quality has to be incorporated in the whole phase of DW development. This paper demonstrates the application of IRADAH (Integrated Requirements Analysis for Data Warehouse) method in implementing data quality into the whole DW development for students admission.Keywords: Data Warehouse, IRADAH, students admission